LOCUS OF CONTROL, STUDY HABITS AND GENDER AS PREDICTORS OF SENIOR SECONDARY SCHOOL STUDENTS ATTITUDE TO PHYSICS IN IBADAN METROPOLIS - Ukoh, Edidiong E; Okeke, Uchenna K (Sokoto Educational Review, 2017)
The study investigated the relationship between Locus of Control, Study Habits, Gender, and Attitude of senior secondary schools physics students in Ibadan metropolis. The study focused on the extent to which Locus of Control, Study Habit and Gender predicted senior secondary schools students Attitude to physics in Ibadan metropolis. The study adopted the descriptive survey research design of the correlational type. The population for the study comprised all senior secondary school 3 (SS3) Physics students in Ibadan Metropolis. Seven hundred and fifty (750) senior secondary 3 (SS3) Physics students were randomly selected from 30 schools in the five local government areas of Ibadan Metropolis. Three instruments were used for data collection. The instruments are Locus of Control Scale (LOCS) with a reliability coefficient of (0.86), Study Habit Questionnaire (SHQ) with a reliability coefficient of (0.89) and Physics Attitude Test Questionnaire (PATQ) with a reliability coefficient of (0.70). Four (4) research questions were raised and answered, using descriptive statistics of mean, inferential statistics of Pearson Product Moment Correlation and Multiple Regression Analysis. Findings of the study showed that the students have an internal Locus of Control. There is a significant composite relationship between the independent variables (Locus of Control, study habits and Gender) and Attitude of students to Physics, with R=.521a, which is equivalent to 52.1%. This indicates a good level of prediction. R2 = 0.271, which is equivalent to 27.1%, indicating the level of shared variance between the dependent variable and the independent variables. Locus of control has the highest contribution with unstandardized coefficient of 0.356 and standardized coefficient of 0.334, while gender has the least contribution with standardized coefficient of .016 and unstandardized coefficient of 0.002. There is a significant relationship between students’ locus of control and students’ attitude to physics [ r=.434, n=750,p=<0.01]. There is no relationship between Gender and Attitude of students to physics [r=-.041,n=750, p=<0.01]. The study concluded that locus of control; study habits and gender are predictors of students’ attitude to physics. The study recommends that necessary instructional methods that will enhance students’ locus of control and study habits be adopted; and gender related issues should be de-emphasis in senior secondary school physics teaching and learning.